Practice in Making Notarial Agreements in Unregistered Marriage in Indonesia - Siti, Bayturrochmah; Sjarif, Fitriani A.; Tardjono, Heriyono (Nurani, 2022)
This article aims to examine the legal force of the marriage agreement deed made by a notary, particular for those who are only married in an unregistered manner. In notary, it is known that there is a Marriage Agreement which is the authority of a notary to prepare an authentic deed in accordance with the provisions of the legislation on the basis of law. Based on the description above, a question arises whether the parties who carry out an unregistered marriage are able to state their wishes in a notarial agreement. What are the possibilities and legal consequences for both the parties and for the notary as a public official who prepares the deed of agreement. The research method uses in this research is normative legal research or normative juridical research with a statutory approach and a case approach. The data used is secondary data, while the analysis method uses qualitative analysis methods. The results of the study indicate that with certain adjustments, a notary is able to prepare a notarial agreement for the parties carrying out an unregistered marriage. The notarial agreement has perfect evidentiary power for the parties as is an authentic deed in general. A notarial agreement with certain adjustments prepared by the parties who entered into an unregistered marriage was prepared with the aim of providing legal protection for the parties.